APAKAH KEPUASAN PELANGGAN DAPAT MEMEDIASI FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN ULANG DI KAYO COFFE AND EATERY?? - Hasrul Fathulloh; Heri Prabowo; Ira Setiawati (Journal of Innovation Research and Knowledge, 2025)
Along with the modern lifestyle, the coffee industry in Indonesia has grown rapidly. Indonesia is also experiencing increased competition. Today, cafes not only provide food or beverages but also offer other services. Based on this explanation, this research was conducted to examine and prove the influence of product quality, price perception, and service quality on repurchase decisions mediated by customer satisfaction—a case study on customers of Kayo Coffee and Eatery. Data processing was conducted using SmartPLS. The hypothesis test results show: There is an influence of product quality on repurchase decisions (P value 0.032 < 0.05). There is an influence of price on repurchase decisions (P value 0.000 < 0.05). There is no influence of service quality on repurchase decisions (P value 0.402 > 0.05). There is no influence of product quality on customer satisfaction (P value 0.064 > 0.05). There is an influence of price on customer satisfaction (P value 0.000 < 0.05). There is an influence of service quality on customer satisfaction (P value 0.000 < 0.05). There is no influence of product quality on repurchase decisions mediated by customer satisfaction (P value 0.073 > 0.05). There is an influence of price on repurchase decisions mediated by customer satisfaction (P value 0.002 < 0.05). There is an influence of service quality on repurchase decisions mediated by customer satisfaction (P value 0.009 < 0.05). There is an influence of customer satisfaction on repurchase decisions (P value 0.000 < 0.05). From the Adjusted R Square values, it is known that the influence of product quality, price perception, and service quality on customer satisfaction is 53.6%, while the influence of product quality, price perception, and service quality on repurchase decisions is 67.6%.